Effects of Chitosan on Clostridium perfringens and Application in the Preservation of Pork Sausage - Shun-Hsien Chang; Ching-Hung Chen; Guo-Jane Tsai (Marine Drugs, 2020)
The effects of chitosan with 95% deacetylation degree (DD95) on the spore germination, cell proliferation, and heat resistance of Clostridium perfringens CCRC 10,648 and CCRC 13,019 were investigated, and its application on pork sausage with sodium nitrite reduction was also evaluated. DD95 chitosan can strongly reduce the heat resistance of both strains. The D80 and D100 values for strain CCRC 13,019 decreased from 40.98 and 4.64 min to 39.21 and 3.26 min, respectively, as a result of adding 250 ppm DD95; meanwhile, addition of chitosan decreased the D80 and D100 values for CCRC 10,648 from 41.15 and 6.46 min to 39.52 and 3.78 min, respectively. In pork sausage, addition of 3000 ppm DD95 chitosan considerably slowed down the bacterial proliferation and volatile basic nitrogen production. There were no significant differences in color (L* and b* values), shearing force, and hardness in the pork sausages with or without DD95 chitosan during storage at 4 and 25 °C. However, the addition of DD95 chitosan in pork sausage significantly retarded the decrease of the a* value. Therefore, DD95 chitosan could reduce the concentration of sodium nitrite required in pork sausages for color retention.